KEMAMPUAN PEMAHAMAN MATEMATIS SISWA PADA MATERI SISTEM PERSAMAAN LINEAR DUA VARIABEL DI SMK PEMBINA BANGSA - Anisah Gustiany; Aniswita Aniswita; Ahmad Fauzan (KOLONI, 2022)
The ability of mathematical understanding is a meaningful ability in mathematical learning, the ability of mathematical understanding is important to students because it can help students think systematically and it can help students solve mathematical problems. The aim of this study is to know the mathematical understanding abilities of high-ability students, medium and low. The study is a descriptive. The participant of this study is X class of AKL SMK Pembina Bangsa there were 15 students. The instrument use in this study is test and interview 6 students of mathematical comprehension. The result of this study is students who have high criteria of mathematical comprehension 67%, medium criteria 20%, and low criteria 13%. Students who have high criteria are able to make an example and state what are known and asked, and students are able to solve that problem well, and able to stated the conclusion of the result found. Students who have medium criteria are just not writing an examples and stating what are known and asked but students are able to complete the operational completion with correct answer, and students can stated the conclusion better, and students who have low criteria are unable to explain the fact and concept of an example, students are unable to state what are known and asked of mathematic models, and students are also unable to combine the previous things with a new things and students are wrong in operating them, and students are not write the conclusion correctly. Keywords: Ability Mathematical Comprehension, Matter SPLDV